Tantangan dan Peluang Pengembangan Keterampilan Bahasa Arab Komunikatif di Pesantren Modern Gontor Putri 4 Sulawesi Tenggara - Imelda Wahyuni (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2018)
What specializes pesantren as an Islamic educational institution is the existence of Arabic language training. In this discourse, pesantren institutional strategy goes important in sustaining santri’s language learning achievement. This paper examines communicative language learning model at Pondok Pesantren Modern Darussalam Gontor Putri 4 of Sulawesi Tenggara. Qualitative-descriptive data were collected through interview and observation. This article explores how pesantren deals with challenge and opportunity to communicative language learning in order to develop santri’s Arabic language ability. Findings show positive language learning achievement because of the availability of educators which are recruited by central management. Various challenges in the learning are managed by developing santri’s commitment to prioritize communicative language efforts. In conclusion, leader’s policy support in elaborating structural and functional of language learning becomes fundamental domain in formulating education program mechanism in pesantren.